Leni Riefenstahl: it is not propaganda… I only showed what was happening - Cercós Raichs, Raquel; Vilanou Torrano, Conrad (Historia y Memoria de la Educación, 2022)
Review of Leni Riefenstahl, por Steve n Bach. Barcelona: Circe, 2008, ISBN: 978-84-7765-261-8 Memorias, por Leni Riefenstahl. Barcelona: Lumen, 2013. ISBN: 978-84-2642-149-4 Conversaciones con Leni Riefenstahl. Almería: Confluencias Editorial, 2016, ISBN: 978-84-945298-7-0 Leni Riefenstahl, por Manuel García Roig. Madrid: Cátedra, 2017, ISBN: 978-84-376-3628-3